Hyper Series

Calculus Level 5

n = 0 ( n + 2 ) ! ( n + 3 ) ! ( n + 10 ) ! n ! = 1 a \sum _{ n=0 }^{ \infty }{ \frac { (n+2)!(n+3)! }{ (n+10)!n! } } =\frac { 1 }{ a }

Find the value of a a .


The answer is 50400.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

Chew-Seong Cheong
Oct 18, 2018

S = n = 0 ( n + 2 ) ! ( n + 3 ) ! n ! ( n + 10 ) ! = n = 0 ( n + 1 ) ( n + 2 ) ( n + 4 ) ( n + 5 ) ( n + 6 ) ( n + 7 ) ( n + 8 ) ( n + 9 ) ( n + 10 ) By partial fraction decomposition = 1 120 n = 0 ( 1 n + 4 12 n + 5 + 50 n + 6 100 n + 7 + 105 n + 8 56 n + 9 + 12 n + 10 ) \begin{aligned} S & = \sum_{n=0}^\infty \frac {(n+2)!(n+3)!}{n!(n+10)!} \\ & = \sum_{n=0}^\infty \frac {(n+1)(n+2)}{(n+4)(n+5)(n+6)(n+7)(n+8)(n+9)(n+10)} & \small \color{#3D99F6} \text{By partial fraction decomposition} \\ & = \frac 1{120} \sum_{n=0}^\infty \left(\frac 1{n+4} - \frac {12}{n+5} + \frac {50}{n+6} - \frac {100}{n+7} + \frac {105}{n+8} - \frac {56}{n+9} + \frac {12}{n+10} \right) \end{aligned}

We note that the sum of nominators 1 12 + 50 100 + 105 56 + 12 = 0 1-12+50-100+105-56+12 = 0 . Therefore,

S = 1 120 ( 1 4 + 1 12 5 + 1 12 + 50 6 + 1 12 + 50 100 7 + 1 12 + 50 100 + 105 8 + 1 12 + 50 100 + 105 56 9 ) = 1 120 ( 1 4 11 5 + 39 6 61 7 + 44 8 12 9 ) = 1 120 × 1 420 = 1 50400 \begin{aligned} S & = \frac 1{120} \left(\frac 14 + \frac {1-12}5 + \frac {1-12+50}6 + \frac {1-12+50-100}7 + \frac {1-12+50-100+105}8 + \frac {1-12+50-100+105-56}9 \right) \\ & = \frac 1{120} \left(\frac 14 - \frac {11}5 + \frac {39}6 - \frac {61}7 + \frac {44}8 - \frac {12}9 \right) \\ & = \frac 1{120} \times \frac 1{420} \\ & = \boxed {\dfrac 1{50400}} \end{aligned}

Syed Shahabudeen
Oct 17, 2018

We can write the given series as n = 0 ( n + 3 1 ) ! ( n + 4 1 ) ! ( n + 11 1 ) ! n ! = x \sum _{ n=0 }^{ \infty }{ \frac { (n+3-1)!(n+4-1)! }{ (n+11-1)!n! } } =\ x , where x x is considered to be its value for the time being ,we know that Γ ( s ) = ( s 1 ) ! \Gamma (s)=(s-1)! therefore the series can also be written as n = 0 Γ ( n + 3 ) Γ ( n + 4 ) Γ ( n + 11 ) n ! = x \sum _{ n=0 }^{ \infty }{ \frac { \Gamma (n+3)\Gamma (n+4) }{ \Gamma (n+11)n! } } =x , we"ll multiply the the LHS and the RHS by Γ ( 11 ) Γ ( 3 ) Γ ( 4 ) \frac { \Gamma (11) }{ \Gamma (3)\Gamma (4) } . i.e Γ ( 11 ) Γ ( 3 ) Γ ( 4 ) n = 0 Γ ( n + 3 ) Γ ( n + 4 ) Γ ( n + 11 ) n ! = Γ ( 11 ) Γ ( 3 ) Γ ( 4 ) x \frac { \Gamma (11) }{ \Gamma (3)\Gamma (4) } \sum _{ n=0 }^{ \infty }{ \frac { \Gamma (n+3)\Gamma (n+4) }{ \Gamma (n+11)n! } } =\frac { \Gamma (11) }{ \Gamma (3)\Gamma (4) } \ x . we know that ( s ) n = Γ ( s + n ) Γ ( s ) { (s) }_{ n }=\frac { \Gamma (s+n) }{ \Gamma (s) } where ( s ) n = s ( s + 1 ) ( s + 2 ) . . . . ( s + n 1 ) { (s })_{ n }\ =\ s(s+1)(s+2)....(s+n-1) is a pochammer notation for rising factorial, so the series can be written as n = 0 ( 3 ) n ( 4 ) n ( 11 ) n n ! = Γ ( 11 ) Γ ( 3 ) Γ ( 4 ) x \sum _{ n=0 }^{ \infty }{ \frac { { (3) }_{ n }{ (4) }_{ n } }{ { (11) }_{ n }n! } } =\frac { \Gamma (11) }{ \Gamma (3)\Gamma (4) } x The series written on the LHS is a gauss hypergeometric series which is of the form 2 F 1 ( α , β ; γ ; 1 ) = n = 0 ( α ) n ( β ) n ( 1 ) n ( γ ) n ( n ) ! { _{ 2 }{ F }_{ 1 }\left( \alpha ,\beta ;\gamma ;1 \right) }=\sum _{ n=0 }^{ \infty }{ \frac { { (\alpha ) }_{ n }{ (\beta ) }_{ n }{ (1) }^{ n } }{ { (\gamma ) }_{ n }(n)! } }
if e ( γ α β ) > 0 \Re e\quad (\gamma -\alpha -\beta ) > 0 the result for this series is n = 0 ( α ) n ( β ) n ( 1 ) n ( γ ) n ( n ) ! = Γ ( γ ) Γ ( γ α β ) Γ ( γ α ) Γ ( γ β ) \sum _{ n=0 }^{ \infty }{ \frac { { (\alpha ) }_{ n }{ (\beta ) }_{ n }{ (1) }^{ n } }{ { (\gamma ) }_{ n }(n)! } =\frac { \Gamma (\gamma )\Gamma (\gamma -\alpha -\beta ) }{ \Gamma (\gamma -\alpha )\Gamma (\gamma -\beta ) } } we came to know that γ = 11 \gamma = 11 , α = 3 \alpha = 3 and β = 4 \beta= 4 therefore we get n = 0 ( 3 ) n ( 4 ) n ( 1 ) n ( 11 ) n ( n ) ! = Γ ( 3 ) Γ ( 11 3 4 ) Γ ( 11 3 ) Γ ( 11 4 ) = Γ ( 11 ) Γ ( 4 ) Γ ( 8 ) Γ ( 7 ) \sum _{ n=0 }^{ \infty }{ \frac { { (3) }_{ n }{ (4) }_{ n }{ (1) }^{ n } }{ { (11) }_{ n }(n)! } =\frac { \Gamma (3)\Gamma (11-3-4) }{ \Gamma (11-3)\Gamma (11-4) } } =\frac { \Gamma (11)\Gamma (4) }{ \Gamma (8)\Gamma (7) } we'll substitute the value of the hypergeometric series on the 4th equation of this solution part therefore Γ ( 11 ) Γ ( 4 ) Γ ( 8 ) Γ ( 7 ) = x Γ ( 11 ) Γ ( 3 ) Γ ( 4 ) \frac { \Gamma (11)\Gamma (4) }{ \Gamma (8)\Gamma (7) } =\quad x{ \frac { \Gamma (11) }{ \Gamma (3)\Gamma (4) } } on solving we"ll get x = Γ ( 3 ) Γ ( 4 ) Γ ( 4 ) Γ ( 8 ) Γ ( 7 ) = ( 2 ) ! ( 3 ) ! ( 3 ) ! ( 7 ) ! ( 6 ) ! = 1 50400 x =\frac { \Gamma (3)\Gamma (4)\Gamma (4) }{ \Gamma (8)\Gamma (7) } =\frac { (2)!(3)!(3)! }{ (7)!(6)! } =\frac { 1 }{ 50400 } so the value of a a as per the question is equal to 50400 50400 i.e a = 50400 \boxed{a = 50400}

I don't think you need to specify a a is an integer.

Chew-Seong Cheong - 2 years, 7 months ago

Log in to reply

sir,i had made the required changes in the question

Syed Shahabudeen - 2 years, 7 months ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...